Localization in Flow of Non-Newtonian Fluids Through Disordered Porous Media - Seybold, H. J.; Eberhard, U.; Secchi, E.; Cisne, R. L. C.; Jiménez-Martínez, J.; Andrade, R. F. S.; Araújo, A. D.; Holzner, M.; Andrade, J.S. (Frontiers in Physics, 2021)
We combine results of high-resolution microfluidic experiments with extensive numerical simulations to show how the flow patterns inside a ``swiss-cheese'' type of pore geometry can be systematically controlled through the intrinsic rheological properties of the fluid. Precisely, our analysis reveals that the velocity field in the interstitial pore space tends to display enhanced channeling under certain flow conditions. This observed flow ``localization'', quantified by the spatial distribution of kinetic energy, can then be explained in terms of the strong interplay between the disordered geometry of the pore space and the nonlinear rheology of the fluid. Our results disclose the possibility that the constitutive properties of the fluid can enhance the performance of chemical reactors and chromatographic devices through control of the channeling patterns inside disordered porous media.